2006
DOI: 10.1200/jco.2005.04.8587
|View full text |Cite
|
Sign up to set email alerts
|

FGFR4 Arg388 Allele Is Associated With Resistance to Adjuvant Therapy in Primary Breast Cancer

Abstract: According to this study, FGFR4 Arg388 genotype is a marker for breast cancer progression in patients with adjuvant systemic therapy, particularly chemotherapy, and thus may indicate therapy resistance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
95
1
2

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 124 publications
(108 citation statements)
references
References 31 publications
8
95
1
2
Order By: Relevance
“…Arg 388 did not correlate with age, HER2, ER and PR status, and grade (Bange et al 2002, Jezequel et al 2004, Thussbas et al 2006, Marme et al 2010. Correlations were found for tumor stage (Thussbas et al 2006, Marme et al 2010, tumor size (Thussbas et al 2006), and axillary lymph node involvement (Bange et al 2002, Jezequel et al 2004, Thussbas et al 2006, Marme et al 2010, but not all of these associations were confirmed by other studies (Bange et al 2002, Jezequel et al 2004, Thussbas et al 2006.…”
Section: Fgfr4supporting
confidence: 77%
See 1 more Smart Citation
“…Arg 388 did not correlate with age, HER2, ER and PR status, and grade (Bange et al 2002, Jezequel et al 2004, Thussbas et al 2006, Marme et al 2010. Correlations were found for tumor stage (Thussbas et al 2006, Marme et al 2010, tumor size (Thussbas et al 2006), and axillary lymph node involvement (Bange et al 2002, Jezequel et al 2004, Thussbas et al 2006, Marme et al 2010, but not all of these associations were confirmed by other studies (Bange et al 2002, Jezequel et al 2004, Thussbas et al 2006.…”
Section: Fgfr4supporting
confidence: 77%
“…Immunohistochemical analysis of breast cancer samples did not show any correlation of the Arg 388 SNP genotype with FGFR4 expression levels (Thussbas et al 2006). Sequence analysis of breast cancer samples revealed that the Arg 388 genotype, either heterozygous or homozygous, was present in 37-43% and 8-11% respectively (Table 3; Bange et al 2002, Jezequel et al 2004, Thussbas et al 2006, Marme et al 2010.…”
Section: Fgfr4mentioning
confidence: 99%
“…Biochemically, this polymorphism influences protein stability and dysregulates FGFR4 signalling at the post-transcriptional level (Wang et al, 2008). Furthermore, expressions of certain polymorphisms or mutations have an impact on the chemosensitivity of tumours (Thussbas et al, 2006;Ansell et al, 2009). Thus, the identification of the Y367C and its consequence of an increased FGFR4 signalling provide an additional mechanism of FGFR4 perturbation that supports tumourigenic activities and hence its value as a potential drug target.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, we identified a single-nucleotide polymorphism in the transmembrane domain of the FGFR4 resulting in a codon conversion from glycine to arginine (G388R), which is homologous to that in FGFR3 causing achondroplasia (Bange et al, 2002). This single-nucleotide polymorphism (SNP) is associated with increased cell motility in vitro as well as lymph node metastasis, advanced tumour stage, resistance to adjuvant therapy and therefore leading to reduced survival of cancer patients (Bange et al, 2002;Thussbas et al, 2006). These findings indicate an important role of FGFR4 in tumour biology.…”
Section: Introductionmentioning
confidence: 99%
“…FGFs serve as special players of certain carcinogenesis process due to their cell proliferating, anti-apoptotic and angiogenic properties. FGFs and FGFRs participate in skin [103] and urothelial carcinogenesis [104]. The MAPK pathway which is triggered by activation of FGFR1 has been related to the proliferation of tumor cells [105].…”
Section: Fgf and Fgfrs: Roles In Cancermentioning
confidence: 99%